Comparison of Maternal and Neonatal Outcomes in Adolescent and Adult Pregnancies in West Java in 2024: A Retrospective Cross-Sectional Study - Chiendo Irine Yulianti; Lies Ani Tambunan; Setyorini Irianti (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: To identify differences in maternal and neonatal outcomes between adolescent pregnancy (ages 16 – 19 years) and adult pregnancy (ages 20 – 35 years) in West Java in 2024.Methods: A retrospective cross-sectional study analyzed 654 singleton pregnancies (adolescents: 16 – 19 years; adults: 20 – 35 years) at Dr. Hasan Sadikin and Cibabat General Hospitals from January to December 2024. Data were analyzed using Chi-square, Fisher’s exact, and Mann-Whitney U tests.Results: Compared to adults, adolescents showed higher rates of preterm delivery (54.5% vs. 49.8%), premature rupture of membranes (30.3% vs. 14.0%), and unintended pregnancies (12.12% vs. 0.64%). Placental abnormalities were observed in 48.9% of adults, compared with 0% of adolescents (p=0.004). No significant differences in neonatal outcomes were found in birth weight (p=0.674), length (p=0.738), APGAR score at 1 minute (p=0.051), and APGAR score at 5 minutes (p=0.137).Conclusion: Adolescent pregnancies have higher maternal complication risks but do not show significant differences in key neonatal outcomes compared to adults. AbstrakTujuan: Penelitian ini bertujuan untuk mengidentifikasi perbedaan luaran maternal dan neonatal antara kehamilan remaja (usia 16 – 19 tahun) dan kehamilan dewasa (usia 20 - 35 tahun) di Jawa Barat pada tahun 2024.Metode: Metode penelitian ini adalah retrospective cross-sectional yang menganalisis 654 kehamilan tunggal (remaja: 16 – 19 tahun; dewasa: 20 – 35 tahun) di Rumah Sakit Umum Dr. Hasan Sadikin dan RSUD Cibabat, Bandung, pada periode Januari–Desember 2024. Data dianalisis menggunakan uji Chi-square, Fisher’s exact, dan Mann–Whitney.Hasil: Remaja memiliki insiden lebih tinggi untuk preterm delivery (54,5% vs. 49,8%), premature rupture of membranes (30,3% vs. 14,0%), dan unintended pregnancy (12,12% vs. 0,64%). Kelainan plasenta ditemukan pada 48,9% dewasa vs. 0% remaja (p=0,004). Tidak ada perbedaan signifikan pada luaran neonatal: berat lahir (p=0,674), panjang badan (p=0,738), APGAR 1 menit (p=0,051), APGAR 5 menit (p=0,137).Simpulan: Kehamilan remaja memiliki risiko komplikasi maternal lebih tinggi tetapi tidak berbeda signifikan pada hasil neonatal utama dibandingkan kehamilan dewasa.